PENGARUH KEJELASAN SASARAN ANGGARAN, PENGENDALIAN AKUNTANSI, SISTEM PELAPORAN DAN PENERAPAN AKUNTABILITAS KEUANGAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (AKIP) (Studi Empiris Pada Satuan Kerja Perangkat Daerah Kabupaten Lima Puluh Kota Provin - Reyhan Hady Fauzan; Azwir Nasir; Sem Paulus Silalahi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research aims to examine the influence of budget goal clarity, accounting control, reporting system and implementation to government performance accountability. The techinique of sampling method is purposive sampling with the sample are the chief of public institution, the chief of financial department and the chief of sub financial department in Lima Puluh Kota public institution. That data are analyzed by linear regression method and SPSS program version 19. The respondents of this research are 85 respondents. The results of this research indicate that budget goal clarity has an effect on performance accountability with 0,000 significance, accounting control has an effect on performance accountability with 0,000 significance, reporting system has an effect on performance accountability with 0,004 significance and financial accountability implementation has an effect on performance accountability with 0,016 significance. The results of this research also showed that coefficient determinant is 46,1%. While the remaining influenced by other variables not included in the regression models were not included in this study as effectivity of system internal control, work motivation and others.Keywords: budget, implementation, accounting, reporting, and government